Family history and breast cancer tumour characteristics in screened women. - Couto, E; Banks, E; Reeves, G; Pirie, K; Beral, V (2008)
Women with a family history of breast cancer have an increased risk of the disease. However, since they tend to experience greater surveillance for the disease, their breast cancers may be detected at an earlier stage, thus making it difficult to assess reliably whether tumour characteristics vary by family history. Information on 9,731 Million Women Study participants with screen-detected breast cancer, diagnosed in 1996-2003, and 37,983 matched controls, who also attended routine screening but were not diagnosed with breast cancer, was used to estimate adjusted relative risks (RRs) of screen-detected breast cancer in women with a family history of the disease. Women with a family history of breast cancer had an increased risk of screen-detected breast cancer (RR 1.57; 95% CI:1.47-1.68) compared with those without such a family history. The RRs were 1.58 (1.46-1.71) and 1.55 (1.34-1.80) for invasive and in situ breast cancer; 1.63 (1.49-1.79) and 1.55 (1.32-1.83) for node-negative and node-positive disease; and 1.56 (1.42-1.70), 1.75 (1.39-2.21) and 1.71 (1.28-2.29) for ductal, lobular and tubular cancers. There was no significant difference in the RR of screen-detected breast cancer associated with a family history of the disease according to invasiveness, size, nodal status, malignancy grade or morphological type of the breast cancer.